Answered step by step
Verified Expert Solution
Question
1 Approved Answer
Part 3-I remember how to catch mistakes! Expression A: (3x^(4))^(2)=6x^(8) Expression B: 4x^(0)=1 Expression C: 5x^(-2)=(1)/(5x^(2)) Expression D: (8x)/(4x^(-1))=2
Part 3-I remember how to catch mistakes! Expression A: (3x^(4))^(2)=6x^(8) Expression B: 4x^(0)=1 Expression C: 5x^(-2)=(1)/(5x^(2)) Expression D: (8x)/(4x^(-1))=2
Step by Step Solution
There are 3 Steps involved in it
Step: 1
Get Instant Access to Expert-Tailored Solutions
See step-by-step solutions with expert insights and AI powered tools for academic success
Step: 2
Step: 3
Ace Your Homework with AI
Get the answers you need in no time with our AI-driven, step-by-step assistance
Get Started